Private Glenleigh Bertie William Skewes : Changi Diary. ([Australia] : Family of Private Glenleigh Bertie William Skewes)
"This is a true story, copied from the Diary entries of VX 61290 - Private Glenleigh Bertie William Skewes of the Australian Army, a Prisoner of War in World War 2. It tells of the trials and experiences of those under the command of the Imperial Japanese Army. Private Glen Skewes was a Medical Orderly attached to the 2/13th Australian General Hospital and, being in this position, he was a witness to the considerable famine and sickness which killed many thousands of fellow servicemen. The original Diary was written on small notebook pages, the latter section being inscribed in diluted purple dye owing to the absence of writing materials. It was constantly hidden from the enemy, and was damaged by the damp and mildew of the monsoon climate. It was carried through the war at great risk as severe punishment was meted out to the person with any such document found upon them. The original Diary is stored at The Australian War Museum, Canberra, Australian Capital Territory. This is the study of an ordinary Australian soldier - his love for his country and his family, his faith in his God, and his feelings for suffering humanity."
Title from title screen (viewed on 29 July 2014)
Mode of access: Available online. Address as at 29/07/14
Selected for archiving
Keywords: Skewes, Glenleigh Bertie William -- Diaries; Changi POW Camp (Changi, Singapore) -- Biography; Prisoners of war -- Singapore -- Changi -- Diaries; World War, 1939-1945 -- Personal narratives; World War, 1939-1945 -- Prisoners and prisons, Japanese; Australian